PENGARUH PENERAPAN AKUNTANSI KEUANGAN DAERAH DAN PENGAWASAN INTERNAL TERHADAP KUALITAS INFORMASI LAPORAN KEUANGAN PADA SATUAN KERJA PERANGKAT DAERAH PROPINSI SULAWESI TENGAH - Nazar, Nazar (Katalogis, 2013)
The objektives of the research were : (1) to identify and analyse the effect of regional finance accounting and internal control toward quality of financial reporting information at Regional Task Force Unit of Central Sulawesi Province, (2) to indentify and analyze the effect of regional finance accounting toward quality of financial reporting information at Regional Task Force Unit of Central Sulawesi Province, (3) to identify and analyze the effect of internal control toward quality of financial reporting information at Regional Task Force Unit of Central Sulawesi Province, (4) to identify and analyse the variables tahat dominantly affect the quality of financial reporting information at Regional Task Force Unit of Central Sulawesi Province. Based on the results of regression test, it was found adjust R Square = 0,610. The value showed the dependent variable can be explained by the implementation of regional finance accounting and internal control was 61 % while the remains 39 % influenced by other variabels which are not discussed in this research model.